"I do not know if Mum knew what was going on": Social reproduction in boarding schools in Soviet Lapland. (3rd July 2018) - Allemann, Lukas
ABSTRACT: This inquiry into the history of boarding schools for indigenous and quasi-indigenous, tundra-connected children in the Soviet part of Lapland tries to answer why children were sent to a boarding school despite their parents living in the same village, and also why an additional school for mentally disabled children, a school half as big as the boarding school for "regular" children, was opened. Data from oral history interviews among former pupils and teachers, both indigenous and incomers, are combined with archival materials. Using the concepts of cynical knowledge as well as the Bourdieuan notions of social exclusion and reproduction, concealed functions of the boarding school system are identified, among which are the attenuation of housing shortage and the operation of the school out of economic interests, alongside with ethnocentric and paternalist patterns. The stigmatization of mostly Sámi children from relocated families as mentally disabled is set in a frame of individualization of the negative, which sought to present failures of the state's social engineering as personal fallibility.